Hydrotherapy as an evidence-based nursing intervention for managing type 2 diabetes mellitus: An integrative review - Yutika Wiguna; Nursiswati Nursiswati; Kusman Ibrahim (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Type 2 diabetes mellitus (DM) is a major global health challenge. Effective management requires non pharmacological interventions in addition to medication. Hydrotherapy, a non invasive and affordable water-based therapy, shows promise in improving blood glucose, insulin sensitivity, and vascular function. This review identifies hydrotherapy interventions for type 2 DM and evaluates their clinical impact. Purpose: To analyze how to improve adherence in type 2 diabetes mellitus patients in implementing the five pillars of diabetes mellitus management. Method: This integrative reviews the size devidence on hydrotherapy for type 2 DM, guided by two questions: "what forms of hydrotherapy intervention are used in the management of type 2 diabetes mellitus?" and "What is the impact of hydrotherapy on clinical out comes for patients with type 2 diabetes mellitus?". The population, intervention, outcome (PIO) frame work was used. A systematic literature search was conducted across major electronic data bases (PubMed, Scopus, Web of Science, EBSCO host: Medline). Seventeen relevant studies were included after screening. Results: Hydrotherapy interventions include hot water baths/immersions, aquaticexercise, hot/cold compression, and oral water consumption. Aquatic exercise can lower HbA1c, fasting glucose, and insulin levels. Hot baths may reduce poor glycemic control and decrease fasting plasma glucose. The tests revealed animmediate decrease in blood glucose. Oral hydrotherapy improved the ankle brachial index. Hydrotherapy also improved quality of life, physical health and reduced stress. The benefits extend to lipid profiles and obesity , as well as blood flow, vascular function, pain, and mobility. Conclusion: Hydrotherapy is a potential complementary intervention for type 2 DM, offering benefits interms of glycemic control, vascular function, quality of life, and physical symptoms. Its non pharmacological, non invasive, afford able, and safe nature make sit a viable nursing option, especially in resource-limited are as. While nurses are crucial in its implementation, current studies have limitations interms of methodology, standardization, and long-term data. Further robust research is needed for widerad option.